DESIGN AND FATIGUE ANALYSIS OF FIXED OFFSHORE PLATFORM BASED ON DNV RP C203 - Pitajeng (15512070) , Rizky
Jacket platform is the most common fixed type offshore platform used in oil exploration and offshore exploitation. One of the platforms which has been built and operated in Indonesia is Platform X. The structure is located in South Mahakam Field with 56,4 meters of depth measured from LAT. The structure design of this platform should follow and meet the applicable international standard to ensure its safety during operation, such as API Recommended Practice and DNV Recommended Practice. The purpose of this final project is to model and analyze the structure of Platform X using SACS (offshore structural analysis and design software). Generally, there were three structural analyses conducted. First, the static in-place analysis was done to calculate the strength of the structure under the operation condition. Seismic analysis was run to test the structural strength to withstand/resist the earthquake load. Fatigue analysis was conducted to calculate the structural strength when loaded with cyclic load. The result of these analyses should meet the standard requirements to be considered as safe. The focus of this final project is the fatigue analysis using DNV RP C203 standard. DNV RP C203 is a standard for fatigue analysis which can be applied for various kinds of joints. Aside from tubular joint, DNV RP C203 is also able to be used for fatigue analysis of conical transition connection and butt weld connection which has a thickness transition between two members of the joint. In fatigue analysis, the criteria that need to be determined based on DNV RP C203 is the value of S-N curve and stress concentration factor (SCF) for every tubular joint, excluding the existed simple tubular joints. In this research, the fatigue life of every joint in the fixed platform structure will be obtained. The fatigue life obtained from using API RP 2A standard will have a different value with the one obtained from using DNV RP C203 standard. For 21year design life, the fatigue analysis which is calculated by using API RP 2A standard generates 162,463 years as the shortest fatigue life for simple tubular joints, while DNV RP C203 generates 282,17 years as the shortest fatigue life for simple tubular joints. These values are inversely proportional with SCF values used on each standard. SCF for tubular joint based on API RP 2A which is calculated automatically by SACS using Efthymiou equation will generate a bigger value compared to the SCF value which is manually calculated using the equation provided in DNV RP C203. Aside from the simple tubular joints, other types of connection, such as conical transition connection and butt weld connection, can be found in this offshore platform structure. Unfortunately, API RP 2A is not applicable for calculating the fatigue analysis on other connections, aside from simple tubular joint. Thus, the calculation of fatigue analysis for other joints will use DNV RP C203 standard. DNV RP C203 provides the equations which can be used to calculate the SCF value of tubular connections other than simple tubular joints. The calculation of conical transition connection and butt weld connection SCF that is based on DNV RP C203 standard will generate a small value of SCF (< 3) so the obtained fatigue life will be very big. The smallest fatigue life of conical transition connection obtained from the analysis is 14668x104 years and 116,236.2 years for butt weld connection. Because of the big value of fatigue life obtained from the analysis of other joints, aside from simple tubular joints, therefore fatigue analysis is not usually conducted on these types of joints during the design planning of offshore platform.